One new species of the genus Xizicus (Orthoptera: Tettigoniidae: Meconematinae) from Chongqing, China - Wang, Hai-Jian; Shi, Fu-Ming (Zootaxa, 2017)
The paper described one new species from Chongqing, China, i.e. Xizicus (Eoxizicus) simianshanensis sp. nov., it resembles Xizicus (Eoxizicus) divergentis (Liu & Zhang, 2000) and Xizicus (Eoxizicus) xiai (Liu & Zhang, 2000), but differs from the latter in: posterior processes of male tenth abdominal tergite straight; inner margin of base area of cerci with a notch, the other area of ventral surface after it enlarged inwards, with distinct edge; subgenital plate with posterior margin narrow, with styli stout and short.